Exclaves - Catudal, Honoré (Cahiers de géographie du Québec, 1974)
The problems raised by territorial fragmentation are perhaps nowhere more acute in instances where a portion of one state, completely surrounded by another, is found to exist. For the exclave or enclave — depending upon one's point of view — disturbs the internal functioning of the surrounding country by, as it were, puncturing a hole in its territory and creates difficulties as well for the administering state.Although the existence of exclaves and enclaves is little known, they are not uncommon phenomena. In fact, there are almost twice the number of exclaves (enclaves) in the world as states.For the most part, these extraordinary territories are rather small, and they do not have large populations. They consist to a great extent of single villages and adjacent lands, farm areas and tiny garden plots. All are situated relatively near to the « mother-land ».It is recognized that the very diminutiveness of these disconnected areas and their lack of strategic significance limits their military and political value. Nevertheless, they do point up the problems of territorial fragmentation and the importance of territorial continuity. Moreover, the way in which states treat them has important implications for those scholars who debate whether or not the « territoriality » of the nation-state is bound to vanish.